The influence of physical exercise on negative emotions in adolescents: a meta-analysis - Wang, Tong; Li, Weicheng; Deng, Jiaxin; Zhang, Qiubo; Liu, Yongfeng (Frontiers in Psychiatry, 2024)
BackgroundAdolescence is also accompanied by ongoing mood changes (relative to childhood and adulthood), which can trigger more extreme negative emotional responses. Physical exercise alleviates negative emotions and reduces the risk of mental illness. However, the effect of physical exercise on negative emotions in adolescents is unclear, so it is valuable to synthesize previous studies with meta-analysis.ObjectiveTo examine the influence of physical exercise (PE) intervention on negative emotions in adolescents aged 10 to 19 years.MethodsWe retrieved the articles from PubMed, Web of Science, EBSCO, Cochrane, and Embase up to April 11, 2024. The main search terms were physical exercise, negative emotions, adolescents, randomized controlled trials. The meta-analysis was conducted using Review Manager 5.3. A random-effects model was employed to calculate the standardized mean difference (SMD) and 95% confidence interval (CI). Subgroups were analysed as the type of negative emotions, type of control group, intervention type, duration, time, frequency.ResultsThe PE intervention group exhibited a significantly superior improvement in alleviating negative emotions compared to the control group (SMD = -0.59, 95% CI: -0.92 to -0.26, p < 0.01, Z = 3.50, I² = 95%). PE was particularly effective in mitigating adolescent depression (SMD = -0.67, 95% CI = -1.07 to -0.28, p < 0.01, I² = 96%) but did not yield significant results in reducing adolescent anxiety (SMD = -0.29, 95% CI = -0.63 to 0.05, p = 0.10, I² = 95%).ConclusionPE intervention can ameliorate negative emotions in adolescents.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024534375.